2023
DOI: 10.1038/s41598-023-27826-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic costimulatory molecule-related signature risk model correlates with immunotherapy response in colon cancer

Abstract: Costimulatory molecules can promote the activation and proliferation of T cells and play an essential role in immunotherapy. However, their role in the prognosis of colon adenocarcinoma remains elusive. In this study, the expression data of costimulatory molecules and clinicopathological information of 429 patients with colon adenocarcinoma were obtained from The Cancer Genome Atlas database. The patients were divided into training and verification cohorts. Correlation, Cox regression, and Lasso regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Comparison of our gene signature with other COAD prognostic models. In order to assess the superiority of our gene signature over other COAD prognostic models, we conducted a comparison of 10 models across the entire TCGA cohort [24][25][26][27][28][29][30][31][32][33] . The 1-year AUC values for all 10 prognostic models were observed, and our findings indicated that our model incorporating the 5 gene signatures had significantly superior predictive power compared to the other 10 prognostic models (Supplementary Fig.…”
Section: Construction and Validation Of Nomogrammentioning
confidence: 99%
“…Comparison of our gene signature with other COAD prognostic models. In order to assess the superiority of our gene signature over other COAD prognostic models, we conducted a comparison of 10 models across the entire TCGA cohort [24][25][26][27][28][29][30][31][32][33] . The 1-year AUC values for all 10 prognostic models were observed, and our findings indicated that our model incorporating the 5 gene signatures had significantly superior predictive power compared to the other 10 prognostic models (Supplementary Fig.…”
Section: Construction and Validation Of Nomogrammentioning
confidence: 99%
“…The immune response to bladder cancer is highly influenced by the interaction between tumor cells and immune cells in the tumor microenvironment. 2,3 As crucial components of the immune system, costimulatory molecules are attracting increasing attention in cancer research. 4 Costimulatory molecules are a group of proteins expressed on the immune cell surface, which regulate the immune response by modulating T-cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…The development and progression of bladder cancer are greatly influenced by the immune system. The immune response to bladder cancer is highly influenced by the interaction between tumor cells and immune cells in the tumor microenvironment 2,3 . As crucial components of the immune system, costimulatory molecules are attracting increasing attention in cancer research 4 …”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research on co-stimulation has made significant progress, leading to the discovery of numerous novel molecules through systematic examinations ( 18 ). However, the target co-stimulatory molecule should be selected with careful consideration as the function of co-stimulation varies among T-cell subsets.…”
Section: Introductionmentioning
confidence: 99%